2010
DOI: 10.1097/pai.0b013e3181c7138b
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cytotoxic and Regulatory T cells in Relapsed/Refractory Hodgkin Lymphoma

Abstract: Recent data suggests the presence of cytotoxic (TIA-1 and granzyme B+) and regulatory T-cells (FOXP3+) in classical Hodgkin lymphoma (cHL) tissues has been shown to correlate with poor overall survival in mainly diagnostic biopsies. By tissue microarray analyses we extend this observation to a cohort of relapsed/refractory cHL tissue biopsies and analyze immunohistochemical expression of FOXP3, TIA-1 and granzyme B in the inflammatory background and the tumor microenvironment. High expression of TIA1 (>50%) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 28 publications
4
24
0
3
Order By: Relevance
“…In this scenario, the malignant B cells would be susceptible to regulation by CD4 + T cells and Tregs. The last hypothesis is supported by several independent studies demonstrating a better survival of patients with B‐cell lymphoma who have a high number of FoxP3 + cells within the tumour 30–38 . Interestingly, several B‐cell malignancies have been linked to autoimmune diseases.…”
Section: Discussionmentioning
confidence: 82%
“…In this scenario, the malignant B cells would be susceptible to regulation by CD4 + T cells and Tregs. The last hypothesis is supported by several independent studies demonstrating a better survival of patients with B‐cell lymphoma who have a high number of FoxP3 + cells within the tumour 30–38 . Interestingly, several B‐cell malignancies have been linked to autoimmune diseases.…”
Section: Discussionmentioning
confidence: 82%
“…4,14,15 Conversely, a higher proportion of regulatory T cells in the CHL microenvironment appears to confer a better prognosis. [16][17][18] The models for these interactions and their relevance to prognosis, however, have been based on cases of sporadic CHL. [18][19][20] Analysis of the cases in this series demonstrated that most cases of immunodeficiency-associated CHL display a predominance of CD163 + histiocytes (ratio of CD163 + /CD68 + cells, 0.66 to 2.8), consistent with an M2 phenotype, 4,21 and high numbers of T-regulatory FOX-P3 lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] The models for these interactions and their relevance to prognosis, however, have been based on cases of sporadic CHL. [18][19][20] Analysis of the cases in this series demonstrated that most cases of immunodeficiency-associated CHL display a predominance of CD163 + histiocytes (ratio of CD163 + /CD68 + cells, 0.66 to 2.8), consistent with an M2 phenotype, 4,21 and high numbers of T-regulatory FOX-P3 lymphocytes. The average number and proportions of CD3 and FOX-P3 lymphocytes in our cases was significantly higher than that reported in cases of CHL not associated with immunodeficiency, 16,17 suggesting differences in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…High numbers of Tregs in the TME correlate with worse prognosis in many types of cancer (Bates et al, 2006;Curiel et al, 2004;Hiraoka et al, 2006). Tregs can also be tumor suppressive as in some B cell cancers; their presence in Hodgkin's Lymphoma correlates with a good prognosis, presumably through a direct suppression of tumor cell growth (Fozza and Longinotti, 2011;Koreishi et al, 2010;Tzankov et al, 2008).…”
Section: T Lymphocytesmentioning
confidence: 99%